Ecocriticism analysis in Eating Our Way To Extinction (2021) documentary film - Utami, Sri Suryanti; Max, Jonathan Irene Sartika Dewi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study aims to analyze how ecological crises are categorized and interpreted through the element of setting in the documentary Eating Our Way to Extinction (2021). The film is selected as the object of study because it emphasizes the urgency of environmental destruction driven by the global food system, particularly practices of animal agriculture that have wide-ranging impacts. This research applies Greg Garrard’s ecocriticism within a qualitative descriptive method, employing categories such as pollution, wilderness, apocalypse, dwelling, animals, and the earth as analytical indicators. Through this framework, the analysis explores how ecological issues are represented not only as scientific facts but also as cultural narratives that shape audience perception. The findings reveal that ecological phenomena including deforestation, biodiversity loss, overfishing, water and air pollution, greenhouse gas emissions, and climate change are interpreted through story, narrative, atmospheric, temporal, and symbolic settings that structure the film’s message. These results demonstrate that setting is not merely a background but a central device that conveys the interconnectedness between human activity and ecological damage, thereby strengthening the persuasive force of the documentary. The study highlights how the use of setting contributes significantly to the film’s ecological discourse and offers a valuable perspective for ecocritical studies of visual media.